Epidemiology of Brucella species in smallholder dairy cattle in selected regions of Tanzania - Mengele, Isaac J.; Akoko, James M.; Shirima, G.M.; Bwatota, Shedrack F.; Motto, Shabani K.; Hernandez-Castro, L.E.; Komwihangilo, D.M.; Lyatuu, Eliamoni; Bronsvoort, B.M. de C.; Cook, Elizabeth A.J. (International Livestock Research Institute, 2024)
Key messages Dairy cattle were predominantly infected with Brucella melitensis Vaccination of cattle and small ruminants recommended Future research needed to develop a bivalent vaccine (B. abortus + B. melitensis) Training required for livestock keepers regarding risky practices & biosecurity measures Further research studies needed on epidemiology of Brucella species circulating in cattle